VitD3-loaded solid lipid nanoparticles: stability, cytotoxicity and cytokine levels - Demirbilek, Murat; Turkoglu, Nelisa Lacin; Akturk, Selcuk; Akca, Cem (TAYLOR & FRANCIS LTD, 2017)
Vitamin D3 (VitD3) has several beneficial effects on many metabolic pathways such as immunity system, bone development. The aim of the study, encapsulation of VitD3 with solid lipids, determine encapsulation efficiency and biocompatibility of nanoparticles. Therefore, VitD3-loaded solid lipid nanoparticles (SLNPs) were developed by optimising ratios of VitD3, stearic acid, beeswax and sodium dodecyl sulphate (SDS). Thermal stability, degradation profile, crystallinity rate, encapsulation efficiency and release profile of SLNPs were determined. Cytotoxicity of SLNPs on HaCaT, L929 and HUVEC cells were investigated. Negatively charged and VitD3-loaded nanoparticles with diameters between 30 and 60 nm were obtained. SLNPs containing up to 5.1 mg VitD3 per 10 mg powder samples were obtained. Cell proliferations were stimulated after exposure with VitD3-loaded SLNPs. Besides, inflammatory response after exposure to VitD3-loaded SLNPs was evaluated via determining IL10 and TNF-alpha levels on THP-1 cells. According to the results, no inflammatory response was observed.
Keywords: Solid lipid nanoparticle; VitD3; inflammation; TRANSDERMAL DELIVERY; DRUG-DELIVERY; VITAMIN-D; ACID; CARRIERS; FORMULATION; PERMEATION; BEESWAX; Chemistry; Engineering; Pharmacology & Pharmacy